Peran Teknologi Digital dalam Monitoring Kesehatan Ternak Ruminansia - I Made Aditya Putra (Lembaga Penelitian dan Pendidikan (LPP) Kalibra, 2025)
The integration of digital technologies in livestock management has become increasingly crucial in improving animal health monitoring, particularly for ruminants. This study aims to explore the role of digital technologies, such as Internet of Things (IoT)-based sensors, wearable devices, machine learning algorithms, and mobile applications, in enhancing livestock health management. A qualitative review approach was employed by synthesizing findings from recent studies published between 2015 and 2024. The results show that digital technologies enable continuous monitoring of physiological parameters, early disease detection, and optimized feed and environmental management. Furthermore, these technologies significantly reduce economic losses due to delayed diagnosis and increase farm efficiency. The discussion emphasizes that integrating digital platforms with veterinary expertise enhances decision-making and ensures sustainable livestock production. In conclusion, the adoption of digital technology for ruminant health monitoring plays a transformative role in precision livestock farming, though challenges remain in terms of cost, infrastructure, and farmer digital literacy. This paper provides both theoretical insights and practical implications for advancing smart livestock farming.